(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
The representation of space is not a mental preconceived form. One must to consider it as a whole of technical, logical and intellectual processes that progress, not very quickly, as the historical and cultural contexts of a society change. Since the Renaissance to the Nineteenth century the representation of architectonic space has crossed fundamental steps, articulated by the scientific thought and technological progress. In this field we analyze the ideas and constructions of the architects and artists that in these centuries the concepts of the science have used. The image, between science and art, opens to a research field about the representation methods of the space and also on the validity of these methods rose and developed in relation to cultural, artistic and social parameters of their time. This paper will deal with images, or better, representations to communicate ideas or tridimensional realities on two–dimensional surfaces. There is a spatial dialogue between art and science, which can be interpreted through six known examples, from the medieval geometry to the fourth–dimension. A sort of excursus of the “point of view” that can synthetically trace the history of these significant works, able to highlight the culture and scientific discoveries of the time that has generated them. From the perspective subjectivism of the “Renaissance box”, which uses the perspective as tool of representation of the Renaissance oligarchy, to the dynamic perspective of the Galileo’s telescope; from the quadraturism of the baroque scene to the reason’s space of Cartesian axes; from the accolade of the technique of Monge’s projections to the figurative vanguards for the experimentation of the fourth–dimension.